Daya Hambat Kombinasi Ekstrak Pegagan (Centella asiatica, L.) dan Peppermint terhadap Pertumbuhan Streptococcus mutans - Lutfi Lailia Sofidiana; Erna Sulistyani; Pujiana Endah Lestari (Pustaka Kesehatan, 2022)
Pegagan leaves and peppermint leaves contain antibacterial and refreshed breath so that the leaves of both these plants have the potential to be used as a mouthwash to prevent many conditions of the oral cavity including caries. One way to reduce the incidence of caries is to use mouthwash that can inhibit the growth of caries-causing bacteria, namely Streptococcus mutans. The use of chemical mouthwash many side effects. Therefore, it is necessary to innovate natural-based mouthwashes that can inhibit the growth of S. mutans with minimal side effects. This study aimed to proved the antibacterial power of the combination of pegagan leaf extract (Centella asiatica) and peppermint leaf (Mentha piperita) in inhibiting the growth of S. mutans. This study used the disc diffusion methode of 4 treatment groups (5%, 10%, 20% and 40% extract), positive control group (chlorhexidine), and negative control group (sterile akuades). Data were analyzed using Kruskal-Wallis Test and Mann-Whitney test. The combination extract of pegagan (Centella asiatica) and peppermint (Mentha piperita) has an antibacterial effect and can inhibit the growth of S. mutans.